2021
DOI: 10.3389/fimmu.2021.737406
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 in SARS-CoV-2 Infection and as a Potential Vaccine Adjuvant

Abstract: IL-7/IL-7R signaling is critical for development, maturation, maintenance and survival of many lymphocytes in the thymus and periphery. IL-7 has been used as immunotherapy in pre-clinical and clinical studies to treat cancer, HIV infection and sepsis. Here, we discuss the critical function of IL-7 in diagnosis, prognosis and treatment of COVID-19 patients. We also summarize a promising role of IL-7 as a vaccine adjuvant. It could potentially enhance the immune responses to vaccines especially against SARS-CoV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Of note, among genes selectively modulated in cytotoxic monocyte subpopulations but not in the others, we identified the IL-7 receptor ( IL-7R ) ( Figure 5F ). Since the recombinant human IL-7 (rhIL-7) has been evaluated as promising vaccine adjuvant against SARS-Cov-2 ( 59 ), we asked whether IL-7R is expressed by all monocytes and upregulated only in the cytotoxic monocytes from moderate patients or if the receptor is selectively expressed by this subpopulation. Interestingly, while other subsets showed low levels of IL-7R , both cMo and ncMo cytotoxic resulted as the most expressing cells ( Figures 5G ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, among genes selectively modulated in cytotoxic monocyte subpopulations but not in the others, we identified the IL-7 receptor ( IL-7R ) ( Figure 5F ). Since the recombinant human IL-7 (rhIL-7) has been evaluated as promising vaccine adjuvant against SARS-Cov-2 ( 59 ), we asked whether IL-7R is expressed by all monocytes and upregulated only in the cytotoxic monocytes from moderate patients or if the receptor is selectively expressed by this subpopulation. Interestingly, while other subsets showed low levels of IL-7R , both cMo and ncMo cytotoxic resulted as the most expressing cells ( Figures 5G ).…”
Section: Resultsmentioning
confidence: 99%
“…These R&D efforts are yet to deliver convincing evidence of their effectiveness. However, anti-PD1/PDL1 and IL-7 therapeutics have shown signs of usefulness and efficacy during clinical trials [ 132 , 133 ]. Thus, similar strategies would be effective in treating SARS-CoV-2 infected patients.…”
Section: Immune-boosting Strategiesmentioning
confidence: 99%
“…Thus, similar strategies would be effective in treating SARS-CoV-2 infected patients. Bekele et al further revealed that IL-7 could aid to protect T cells from death, promote the proliferation of T cells, and support reversing lymphopenia in SARS-CoV-2 infected patients suffering from sepsis [ 133 ].…”
Section: Immune-boosting Strategiesmentioning
confidence: 99%
“…There are contradictory interpretations regarding the role of IL-7; in fact, evidence supports a beneficial role in COVID-19 as demonstrated in a small group of critically ill patients where the administration of IL-7 induced an increase in lymphocyte count without causing either lung damage or evident hyperinflammation [ 15 ]. A role for this cytokine as vaccine adjuvant has also been proposed [ 16 ]. Nevertheless, the augmentation of IL-7 above physiological levels may have a detrimental role disrupting the immunobalance [ 17 ].…”
Section: Discussionmentioning
confidence: 99%